Making and Breaking Habits: Teaching (and Learning) Cultural Context, Self-Awareness, and Intercultural Communication Through Case Supervision in a Client-Service Legal Clinic - Antoinette Sedillo López (Washington University Journal of Law & Policy, 2008)
This Essay begins by offering teaching objectives that can be used to focus supervision and education on effective representation of clients from different cultures as issues arise in the course of representation. Culture is a term used not in the anthropological sense, but rather in the sense of differences between individuals that are related to different backgrounds, value systems, religions, classes, ethnicities, races, or other factors that contribute to a person’s experience of the world. The Essay then discusses the context of student supervision and explains how case supervision sessions can be extremely effective moments during which to pursue those teaching goals. It makes suggestions for the most effective stages of supervision in which to address issues of difference. The Essay next examines vignettes that grew out of cases handled by the University of New Mexico’s Clinical Law Program. The vignettes identify cultural issues that have come up in the clients’ cases and suggest ways that effective supervision might be used to help the student develop cultural context, self-awareness, and intercultural communication skills as part of the clinical supervision experience. This Essay seeks to add to the growing literature about the importance of these areas in legal education.
Keywords: Clinical legal education; Cross-cultural differences; Cross cultural training; Educational programs; Intercultural communication; Race awareness; New Mexico; United States